Pemberdayaan Orang Tua Dan Guru Dalam Membangun Early Warning System Terhadap Kejahatan Seksual Pada Anak Di Tk Sd Model Kabupaten Sleman - Wahyuni, Kenik Sri; Ceria, Inayati; Verawati, Bernadeta; Mahanani, Setyo (Universitas Respati Yogyakarta, 2020)
The development of technology which is rapidly increasing has an impact on children. One of the problems that lurk children is the case of child sexual abuse. The number of cases of sexual crimes against children requires an integrated effort both at home by parents and at school by teachers. But in reality, these activities are hampered by the absence of structured BK implementation in primary schools. Although there are already formal rules governing BK in basic education. The absence of special hours for guidance and counseling in elementary school also becomes an obstacle in providing information services for students. In addition, limited knowledge and misperceptions of parents about reproductive health education in children. Activities carried out by training methods. This dedication partner is TK Model SD Sleman Regency Yogyakarta, where the target of the activity of this training are TK Model SD teachers and representatives of student guardians as well as students / students. The purpose of the activity is to empower the target to be able to become a role model in providing sexual education and reproductive health for children / students. the results of this PKM activity are the BK module, the availability of child-friendly and easily accessible reproductive health promotion media, the availability of adequate BK rooms, the increase in the knowledge and skills of teachers and parents in providing sexual education / child reproductive healthKeywords:Â Education, reproductive health, childrenÂ